Assessing the sustainability of spatial development decisions - Kocziszky, György; Szendi, Dóra (Észak-magyarországi Stratégiai Füzetek, 2023)
Changing social and economic conditions justify a rethinking of the theory and practice of domestic spatial development and planning. Despite the progress made over the last thirty years, sustainability problems have emerged for some development projects following the exhaustion of budgetary resources. This paper presents a model developed by the authors for the ex-post and ex-ante assessment of the sustainability of spatial development decisions and suggests an aggregate index for quantifying the model, which can be used to support the preliminary analysis for spatial development decisions.